The Effectiveness of Listening Journal on Speaking Ability - Azizah, Maratul; Jayani, Nanang (Faculty of Teacher Training and Education of Undaris, 2025)
This study examines the effectiveness of using listening journals to students speaking ability. At this moment,researchers were used the listening journal to facilitate learning how to speak. The researchers tested whatthe effect of the treatment would be on students' speaking abilities. The participants consist of 10 male and15 female English education students of IAI Nusantara Ash-shidiiqiyah. Data was gathered using a test todetermine the students' speech level. This research was under descriptive quantitative, using a pre-experimental design with a center on the sort of one group pretest-posttest design. The information wasdisplayed by the significance of hypothesis testing which appears that the Sig. (2-tailed) the significance ofthe report is 0.000 less than the level of value 0.05. Therefore, the null hypothesis was rejected and thealternative hypothesis was accepted. The results showed that there was an impact use of listening journalmedia on students' speaking skillsKeyword; listening journal, speaking ability